Antimicrobial Properties of Acrylic Resin Incorporated with Propolis Nanoparticles - Sepideh Arab; Abbas Bahador; Ahmad Sodagar; Maryam Pourhajibagher; Azam Akhavan; Aseel Niema Hafith; Tahereh Pornamazeh (Tehran University of Medical Sciences, 2021)
Objectives: One of the main problems with polymethyl methacrylate (PMMA) used for the fabrication of oral removable appliances is plaque accumulation due to surface porosities. Incorporation of antimicrobial agents in this material might help tackle this problem. The aim of this study was to evaluate the antimicrobial activity of PMMA acrylic resin incorporated with propolis nanoparticles (PNPs). Materials and Methods: Antimicrobial properties of acrylic resin incorporated with PNPs were assessed against Streptococcus mutans (S. mutans), Streptococcus sanguinis (S. sanguinis), Lactobacillus acidophilus (L. acidophilus) and Candida albicans (C. albicans). Acrylic discs were fabricated in four groups: A control group without PNPs and three experimental groups containing 0.5%, 1% and 2% concentrations of PNPs. Disc agar diffusion (DAD) test was performed to determine the antimicrobial effects of PNPs by measuring the microbial growth inhibition zones on Muller-Hinton agar plates. The eluted components test evaluated the viable counts of microorganisms in liquid medium after 24 and 72h. Finally, biofilm inhibition test assessed the efficacy of PNPs for inhibition of biofilm formation. P<0.05 was considered significant.  Results: The acrylic discs failed to produce microbial inhibition zones in the DAD test. Discs containing 1% and 2% nanoparticles showed anti-biofilm effects on all four microbial species. The colony counts of all microorganisms significantly decreased following exposure to liquids containing nanoparticles after 24 and 72h in eluted component test. Conclusion: PMMA acrylic discs incorporated with PNPs presented some antimicrobial properties against S. mutans, S. sanguinis, L. acidophilus, and C. albicans